Купцы-скандинавы и Киевская Русь на пути в Византию в Х–XI вв. - Мельникова, Е.А. (Хазарский альманах, 2020)
The absence of any information about trade voyages of Scandinavians to Byzantium in the 10th to 12th centuries AD in Old Norse written sources asks for an explanation especially as there exist multitude of mentions of Scandinavians serving as mercenaries there. The article aims to demonstrate that the free access to Byzantine markets was blocked by the Kiev princes for ‘independent’ merchants. The new warrior elite of the emerging Middle-Dnieper polity depended on the war-and-trade economy and the realization in Byzantine of the goods acquired as tributes was a vital necessity for it. This radical measure eliminated competitors who could signifi cantly diminish the profi ts of the Kiev Rus’.